2010
DOI: 10.3354/ab00227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organochlorines on cytochrome P450 activity and antioxidant enzymes in liver of roundnose grenadier Coryphaenoides rupestris

Abstract: Oceans function as a sink for organochlorine compounds (OCs) such as PCBs and DDTs. Deep-sea fish bioaccumulate OCs to levels 10 to 100 times higher than shallow-water species. OCs induce the cytochrome P450 (CYP) system, the activity of which may increase reactive oxygen species (ROS) production in liver cells. However, the susceptibility of fish to the oxidative stress likely caused by OCs remains unclear. We analysed whether PCB and DDT contamination of roundnose grenadier Coryphaenoides rupestris was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Therefore, the main focus of the present study was to assess the stress-mitigating role of dietary pyridoxine on endosulfan exposure of C. chanos. The exposure to organochlorine pesticides is linked with increased cytochrome P-450 (CYP) 1A1, a source of reactive oxygen species (ROS), and it is measured by 7-ethoxyresorufin-O-deethylase (EROD) activity [40,41]. Further, the activities of antioxidative enzyme (SOD and catalase) protect cells against oxygen radical damage, and the activities of phase II conjugating enzymes viz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the main focus of the present study was to assess the stress-mitigating role of dietary pyridoxine on endosulfan exposure of C. chanos. The exposure to organochlorine pesticides is linked with increased cytochrome P-450 (CYP) 1A1, a source of reactive oxygen species (ROS), and it is measured by 7-ethoxyresorufin-O-deethylase (EROD) activity [40,41]. Further, the activities of antioxidative enzyme (SOD and catalase) protect cells against oxygen radical damage, and the activities of phase II conjugating enzymes viz.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the activities of antioxidative enzyme (SOD and catalase) protect cells against oxygen radical damage, and the activities of phase II conjugating enzymes viz. GST also increase under pesticide stress , and it helps in the conjugation of products of phase I xenobiotic metabolism. The same results have been observed in the present study as well as in our earlier work .…”
Section: Discussionmentioning
confidence: 99%
“…A negative trend was revealed between CAT and EROD activities in the six compared species (r = −0.692; p N 0.05) but instead it was significantly and positively correlated to the CYP-related ECOD activity (r = 0.872; p = 0.023). In former studies a good correspondence between CAT and EROD activities was documented in deep-sea fish (Lepidion lepidion, Coryphaenoides guentheri and Bathypterois mediterraneus) in Porte et al (2000); as well as in the deep-sea macrourid Coryphaenoides rupestris (Lemaire et al, 2010) but in these reported cases, a pollution gradient was considered.…”
Section: Effects Of Environmental and Biological Variables On Biotranmentioning
confidence: 92%
“…In 1986 Stegeman et al, reported a correlation between levels of hepatic CYP1A (aka P450E) and EROD activity, and the levels of polychlorinated biphenyls in C. armatus , consistent with induction of CYP1A in this species in situ in the deep ocean [63]. Studies also suggested chemical induction of CYP1A in a congeneric though less deep-living species C. rupestris (200 – 2600 m depth) [67]. However, the extent of CYP1A increase in liver slices of C. rupestris exposed to an AHR agonist suggests that the induction response could be diminished under pressure [68].…”
Section: Discussionmentioning
confidence: 99%